The discourse of professional identity in child and adolescent mental health services - Baldwin, Laurence James (2008)
Background: Child and adolescent mental health teams have traditionally been constructed using multidisciplinary teams of different professions. Current workforce policy in mental health, however, stresses team function and the skills and competences required to fulfil that function which leads to a questioning of professional identity within those teams.